Biomotor Profile of Taekwondo Athletes Poomsae Putera Age Under 14 years in East OKU Regency 2019 - Noviria Sukmawati (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The purpose of this study is to find out: Biomotor Profile of Taekwondo Poomsae Athletes of Children Under 14 Years of Age in East OKU Regency in 2019. This research is a survey method, while the techniques and data collection use tests and measurements. The study subjects consisted of 13 people with age categories under 14 years. The results showed the data is based on the T Score in the category of very less percentage of 7.69% (1 athlete), in the category of less percentage of 38.46% (5 athletes), in the medium category a percentage of 15.38% (2 athletes), a good category of percentage of 23.08% (3 athletes), and very good category with a percentage of 15.38% (2 athletes). Based on the results of the analysis that the biomotor profile of male Poomsae taekwondo athletes based on the average value is included in the medium category, so for the trainers and athletes themselves to add more hours especially to do exercises related to taekwondo biomotor. Keywords: Biomotor, Putera Athlete, Poomsae, Age 14 years